Rituximab as a therapeutic option for patients with advanced melanoma - Winkler, Julia K.; Schiller, Matthias; Bender, Carolin; Enk, Alexander; Hassel, Jessica C. (Cancer immunology immunotherapy, 2018)
Treatment of metastatic melanoma remains challenging, despite a variety of new and promising immunotherapeutic and targeted approaches to therapy. New treatment options are still needed to improve long-term tumour control. We present a case series of seven patients with metastatic melanoma who were treated individually with the anti-CD20 antibody rituximab between July 2014 and July 2015. Two of the patients were treated in an adjuvant setting. All patients had already received a variety of treatments. During an induction phase, the administration of four cycles of weekly rituximab 375 mg/m2 body surface area was planned. After imaging, patients with stable disease continued therapy with rituximab 375 mg/m2 body surface area every 4 weeks up to a maximum of 24 weeks. Two patients experienced grade 2 infusion reactions during the first infusion. Otherwise, treatment was well tolerated and there were no grade 3 or 4 side effects. Staging after the induction phase showed stable disease in five patients, and two patients had progressive disease. Median progression-free survival was 6.3 months (95% CI 4.97-7.53), median overall survival was 14.7 months (95% CI 4.52-24.94), and one patient was still alive in December 2016. In conclusion, rituximab might be a therapeutic option for metastatic melanoma. However, further studies on rituximab among larger patient cohorts are warranted. Evaluation of therapy in an adjuvant setting or in combination with other systemic treatment might, therefore, be of particular interest.